Apocrine secretion by the choroid plexus - Ya’el Courtney; Maria K. Lehtinen (Fluids and Barriers of the CNS, 2025)
Abstract The choroid plexus (ChP) epithelium secretes cerebrospinal fluid (CSF) and signaling factors that influence brain development. In addition to classical secretory pathways, the ChP also employs apocrine secretion, in which large cytoplasmic portions bud from the apical surface in structures called aposomes. Although historically underappreciated, recent imaging and molecular studies demonstrate that this process is calcium-dependent and regulated by neuromodulators such as serotonin. Apocrine secretion contributes distinct cytoplasmic cargo—proteins, organelles, and signaling molecules—to the CSF, with evidence for developmental roles in neurogenesis and progenitor cell differentiation. This review synthesizes structural, functional, and proteomic data supporting ChP apocrine secretion, compares it to other epithelial release mechanisms, and highlights outstanding questions about its regulation and physiological roles. By focusing on this unconventional and understudied mode of secretion, we provide a framework for understanding how ChP-mediated cargo release shapes the CSF environment and contributes to brain development.